2022
DOI: 10.1002/ehf2.14171
|View full text |Cite
|
Sign up to set email alerts
|

Familial risk of dilated and hypertrophic cardiomyopathy: a national family study in Sweden

Abstract: AimsThis study aims to determine the familial incidence of dilated (DCM) and hypertrophic cardiomyopathy (HCM) in firstdegree, second-degree, and third-degree relatives of affected individuals. Methods and resultsIn this population-based multigenerational cohort study, full-siblings, half-siblings, and cousin pairs born to Swedish parents between 1932 and 2015 were included, and register-based DCM and HCM diagnoses among relatives were ascertained. Adjusted odds ratios (ORs) for DCM and HCM were calculated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…A previous GWAS for coronary artery diseases (CADs) or angina pectoris included VSA; however, no stratified analyses have been performed specifically for VSA, to our knowledge. A recent Swedish nationwide study reported high familial heritability for VSA, highlighting the importance of investigating genetic susceptibility. This study aimed to identify genetic factors associated with VSA, and uncover the specific underlying pathologies of VSA.…”
Section: Introductionsupporting
confidence: 82%
“…A previous GWAS for coronary artery diseases (CADs) or angina pectoris included VSA; however, no stratified analyses have been performed specifically for VSA, to our knowledge. A recent Swedish nationwide study reported high familial heritability for VSA, highlighting the importance of investigating genetic susceptibility. This study aimed to identify genetic factors associated with VSA, and uncover the specific underlying pathologies of VSA.…”
Section: Introductionsupporting
confidence: 82%
“…Furthermore, it is noteworthy that while the onset of disease occurs later in women, they face an elevated risk of developing heart failure or death ( 105 ). These observations also suggest that women may require a higher number of genetic alterations to develop heart failure, implying an increased likelihood of transmitting the disease to their offspring ( 106 ).…”
Section: Genetic Differencesmentioning
confidence: 99%
“…Genetic testing shows that a higher percentage of women carry sarcomere gene variants, with variable effects on disease presentation and progression based on the specific gene variant. In a nationwide family risk study, researchers observed that the relatives of female patients with HCM are more likely to be affected by the disease compared to the relatives of affected males [78]. This finding suggests the possibility of a multifactorial threshold model of inheritance, in which female individuals carry a higher genetic load for HCM.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…Consequently, females would be more likely to transmit the disease to their offspring and have siblings with the disease. This phenomenon is referred to as the Carter effect [78]. This suggests that the genetic factors contributing to HCM susceptibility may differ between males and females, with females requiring a higher genetic burden to manifest the disease.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%